Determinants of uterine rupture among mothers who gave birth in Jinka and Arba Minch General Hospitals, institution-based case–control study, Southern Ethiopia, Ethiopia, 2019. (September 2020) - Girmay, Goitom; Gultie, Teklemariam; Gebremichael, Gebrekiros; Afework, Bezawit; Temesgen, Gebremariam
Background: Uterine rupture is a major public health problem in low-income countries including Ethiopia. In Ethiopia, its prevalence is low, but it results in devastative health problems of the mother and her baby. Even though the Ethiopian government and nongovernmental organizations tried to strengthen the health care system, significant adverse maternal and fetal outcome is still associated with uterine rupture. The aim of this study was to identify determinants of uterine rupture in Jinka and Arba Minch General Hospitals. Methods: The study was conducted in Jinka and Arba Minch General Hospitals, and the data collection period was 15 to 30 November 2018. A case–control study design was used with simple random sampling of 1:4. Data were collected using data extraction sheets. Variables with p < 0.25 in bivariate logistic regression were entered into multivariable logistic regression. Variables with p < 0.05 in multivariable logistic regression were used to determine significant association between dependent and independent variables. Result: Uterine rupture occurred in 112 cases with 448 controls. Women referred from health facilities (adjusted odds ratio = 8.0, 95% confidence interval: 3.5–17.8), multiparous women (adjusted odds ratio = 12.7, 95% confidence interval: 4.2–39.0), duration of labor more than 18 h (adjusted odds ratio = 11.5, 95% confidence interval: 5.5–24.1), malpresentation (adjusted odds ratio = 3.5, 95% confidence interval: 1.0–8.0) and gestational age of ⩾37 weeks (adjusted odds ratio = 5.2, 95% confidence interval: 1.4–19.3) were independent factors associated with uterine rupture. Conclusion: Mothers referred from health facilities, multiparous women, duration of labor more than 18 h, gestational age of ⩾37 weeks and malpresentation were significantly associated with uterine rupture. Early referral, encouraging family planning, proper use of partograph, early identification and appropriate intervention for malpresentation are recommended.